2012
DOI: 10.3109/00016489.2012.694473
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular-evoked myogenic potential in response to bone-conducted sound in patients with otosclerosis

Abstract: Conclusion:Saccular dysfunction is a major cause of balance problems in patients with otosclerosis. Vestibular-evoked myogenic potential in response to bone-conducted sound (BC-VEMP) testing is useful for diagnosis of these patients.Objectives:The purpose of this study was to elucidate the origin of balance problems in patients with otosclerosis using BC-VEMP.Methods:Subjects comprised 25 patients with unoperated otosclerosis (9 men and 16 women). They were divided into two groups depending on type of balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…A 2012 study by Saka et al [33] found that balance problems in otosclerosis were associated with abnormal results for BC-VEMP. Conversely, the present analysis of 74 patients with otosclerosis, relying on the assessment of a higher clinical sample than other prospective studies, could not support this theory based on VEMP only.…”
Section: Discussionmentioning
confidence: 99%
“…A 2012 study by Saka et al [33] found that balance problems in otosclerosis were associated with abnormal results for BC-VEMP. Conversely, the present analysis of 74 patients with otosclerosis, relying on the assessment of a higher clinical sample than other prospective studies, could not support this theory based on VEMP only.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the design, eight (29%) studies were descriptive (5)(6)(16)(17)(18)28,(30)(31) ,19 (68%) were comparative cross-secti onal (7)(8)(9)(10)(12)(13)(14)(15)(19)(20)(21)29,(32)(33)(34)(35)(36)(37)(38) , and one (3%) was longitudinal cohort (39) .…”
Section: Methods Characterization Applicationmentioning
confidence: 99%
“…Concerning the type of applied stimulation, the number (%) of studies using the sound or the electric stimulation were: 19 (68%), auditory -rarefaction tone burst (6)(7)9,12,(14)(15)(16)(17)(18)21,(28)(29)(30)(31)33,(35)(36)(38)(39) ; three (11%), auditory -rarefaction tone burst and click (8,13,32) ; two (7%), auditory -click (10,37) ; two (7%), galvanic (20,34) ; one (3.5%), auditory -click and galvanic (5) ; one (3.5%), auditory -rarefaction tone burst and galvanic (19) . The electric current intensity of galvanic stimulation ranged from 1 to 5 mA (5,19,20,34) .…”
Section: Methods Characterization Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been demonstrated that the elicitability of AC cVEMPs is reduced in otosclerotic patients, most likely because of respectively conductive hearing loss and inner ear impairment (22,23) and that this might correlate with the progression of otosclerosis (22). Also, BC cVEMPs show a lower response rate in otosclerosis (22,24), and a higher frequency of abnormal BC cVEMPs is observed in otosclerotic patients with dizziness than in patients without symptoms (25). When cVEMPs were compared before and after stapes surgery in otosclerosis patients, Trivelli et al (23) found no difference in response rate in both AC and BC cVEMPs, and Singbartl et al (24) show reappearance of the BC cVEMP in 3 of 23 patients after stapes surgery.…”
mentioning
confidence: 95%